Thermoelectric power source for electronic medical thermometer - L. I. Anatychuk; R. R. Kobylianskyi; I. A. Konstantinovich (Tekhnologiya i Konstruirovanie v Elektronnoi Apparature)
At present chemical sources of electricity are used as power supplies for low-powered electronic equipment. Despite continuous quality improvement (CQI) of chemical sources of electricity they still have some critical faults, such as: relatively high specific overall dimensions, presence of self-discharge, short life and limited shelf life under low temperature storage. Moreover, the chemical source of electricity production is power-consuming, costly and environmentally harmful. The plurality of facts given above stipulates the search for new sources of electric energy eliminating the faults chemical ones possess. Therefore, thermoelectric power supply sources are especially prospective in this respect as thermoelectric generators in general have a long operational life, they are reliable for use in extreme conditions and do not need being changed periodically. It is a well-known fact that thermoelectric converter efficiency depends on the load resistance and the converter resistance matching, which are stipulated by such converter design. The results of calculations of a thermoelectric converter for a medical thermometer power supply are presented in this paper. The authors define a rational design of such a converter which is limited by technological complexity of small-size legs fabrication, on the one hand, and with the converter overall dimensions, on the other hand. The study carried out has shown the expediency of a thermoelectric converter application for various operational modes to provide an electronic medical thermometer power supply, particularly in the unmatched load mode with the converter efficiency dropping five to tenfold. The work confirms the possibility of a thermoelectric converter of human body application for an electronic medical thermometer power supply.